Redeployment of odontode gene regulatory network underlies dermal denticle formation and evolution in suckermouth armored catfish - Shunsuke Mori; Tetsuya Nakamura (Scientific Reports, 2022)
Abstract Odontodes, i.e., teeth and tooth-like structures, consist of a pulp cavity and dentin covered by a mineralized cap. These structures first appeared on the outer surface of vertebrate ancestors and were repeatedly lost and gained across vertebrate clades; yet, the underlying genetic mechanisms and trajectories of this recurrent evolution remain long-standing mysteries. Here, we established suckermouth armored catfish (Ancistrus sp.; Loricariidae), which have reacquired dermal odontodes (dermal denticles) all over most of their body surface, as an experimental model animal amenable to genetic manipulation for studying odontode development. Our histological analysis showed that suckermouth armored catfish develop dermal denticles through the previously defined odontode developmental stages. De novo transcriptomic profiling identified the conserved odontode genetic regulatory network (oGRN) as well as expression of paired like homeodomain 2 (pitx2), previously known as an early regulator of oGRN in teeth but not in other dermal odontodes, in developing dermal denticles. The early onset of pitx2 expression in cranial dermal denticle placodes implies its function as one of the inducing factors of the cranial dermal denticles. By comprehensively identifying the genetic program for dermal odontode development in suckermouth armored catfish, this work illuminates how dermal odontodes might have evolved and diverged in distinct teleost lineages via redeployment of oGRN.